Pengaruh Metode Gamifikasi Terhadap Kemampuan Komunikasi Dan Berpikir Kritis Siswa Kelas Iv Dalam Pembelajaran Bahasa Indonesia - Ghina Nursa’adah; Inayatul Ummah; Dadan Setiawan (Jurnal Sultra Elementary School, 2024)
This study aims to analyze the impact of gamification methods on the communication and critical thinking abilities of Grade IV students in Indonesian language learning at MI Miftahul Ulum Karangsari. Using a quantitative approach with a quasi-experimental design, the research involved two groups: an experimental group that applied the gamification method and a control group that used conventional teaching methods. Data collection was carried out through observation and tests (pre-test and post-test). The results showed that the gamification method had a significant positive effect on improving students' communication and critical thinking skills. The experimental group demonstrated greater improvement in both communication skills (mean 41.07) and critical thinking ability (mean 79.29) compared to the control group (mean 33.38 for communication and 55.58 for critical thinking). These findings highlight the potential of integrating game elements into Indonesian language learning to enhance student engagement and cognitive skills, particularly in communication and critical thinking.